(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
Knee injuries are one of the most common problems among athletes in game sports such as football, basketball, handball and volleyball. Given the high loads on the musculoskeletal system during rapid movements, jumps and sudden changes in the direction of movement, athletes of these sports often suffer damage to the structures of the knee, including the menisci, ligaments and cartilage. The purpose of the study: to develop a program to improve the functional state of the knee joint in athletes of game sports after arthroscopic treatment and experimentally evaluate its effectiveness. Research methods. Theoretical research methods were used in the work: analysis, comparison, induction, deduction, systematization and generalization of scientific and methodical literature, pedagogical experiment, medical and biological methods, methods of mathematical statistics. Work results. At the end of the study, the index of knee joint flexion in athletes of the main group was significantly higher compared to the control group by 25.74 degrees (p<0.001), and extension by 14.30 degrees (p<0.001). In the control group, changes in knee flexor strength were not statistically significant, with an improvement of 0.35 points (p>0.05), while extensor strength increased by 0.25 points (p>0.05). In the main group, there was a significant improvement in the strength of the knee joint flexors by 1.82 points (p<0.001), and the strength of the extensors - by 1.90 points (p<0.001). At the end of the study, after the operation, pain sensations in both groups became close to normal indicators, however, in the main group, the level of pain syndrome was significantly lower than in the control group. Conclusions. Thus, the results of the study testify to the importance of the use of specialized physical rehabilitation programs to achieve optimal results in the recovery of athletes after arthroscopic operations.